Prevalenca čezmerne prehranjenosti in debelosti med pet let starimi otroki in 15 oziroma 16 let starimi mladostnicami in mladostniki v Sloveniji - Avbelj, Magdalena (Zdravniški vestnik, 2005)
Background. In the last twenty years a marked rise in overweight and obesity among children and adolescents in developed countries was observed. Obesity inthis age group is a significant risk factor for type 2 diabetes and cardiovascular diseases in adulthood. So far no comparative data on overweightand obesity in Slovene children and adolescents existed. In our study the data collected during preventive examinations of five-year-old and adolescents was analysed and guidelines for management of children with high body mass index (BMI) were proposed. Methods. Using the methods of descriptional statistics the data on BMI of 4685 randomly collected five-year-old children and 2474 randomly collected adolescents aged 15-16 years were analysed. Data was collected in the years 2003-2005, evaluated according to the international reference values, and compared to other populations. Results. The prevalence of overweight among five-year-old children is 18.4% and 20.9% in boys and girls respectively. The obesity criteria are fulfilled in 9.0% boys and 7.9% girls. Among adolescents 17.1% boys and 15.4% girls are overweight and 6.2% boys and 3.8% girls are obese. These results indicate that the prevalence of obesity in Slovenia is similar as in other developed European countries. Conclusions. The study showed that obesity in childhood and adolescence in Slovenia is a problem that deserves more concern in medical institution and on national level. Further research onreasons for this condition and new programs for stimulation of physical activity and healthy nutrition of children and adolescents are warranted.
Keywords: Adolescenca; Adolescence; Body Height; Body Mass Index; Body Weight; child; Child, Preschool; Debelost; Epidemiology; mladostniki; Obesity; otroci; Otrok predšolski; Prevalenca; Prevalence; Telesna masa, indeks; Telesna teža; Telesna višina